Municipal Wastewater Management - Prochaska, Charikleia (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Taking the papers' collection of this Special Issue as a whole, it is clear that "Municipal Wastewater Management" is an ongoing field of research with the ability to incorporate current environmental and human health challenges. The use of municipal sewage to monitor COVID-19 virus circulation in communities and the estimation of possible outbreaks, even before clinical cases have been identified, is a fact that justifies this. In light of the Coronavirus pandemic, the interest of the impact that research on municipal wastewater management can have on improving humans' health and protecting the environment is being rethought. In respect to this, there is an essential need for scientific publications that present varieties of case studies and discuss best practices, so as wastewater treatment plants to be seen not only as sites of pollutants removal but also as places where energy is efficiently used and environmental sustainability is being practiced, in close relation to the needs of the community. Viewed in this way, the papers' collected in this Special Issue are looking forward to reach a broad readership that can gain awareness and understanding of their topics and be stimulated into future research and collaborations that would improve all stakeholders engagement in promoting a sustainable municipal wastewater management.